Histoire d’os : Étude et restauration de deux boîtes ostéologiques - Élodie Beaubier (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The “osteology boxes” such as they were presented to the National Natural History Museum of Paris, reflected the various theories of "the evolution" during the nineteenth century. They present the bones, methodically arranged, of the skull of one or several species. We studied the various possibilities for the cleaning process of the ancient bones, as well as the restoration of the patrimonial collections of Natural history museums.